Improving the Methodological Competence of the Future Teacher of English in the Conditions of Modern Information Technologies - Djanabaeva Adina; Urazova Marina Batirovna (Genius Journals, 2023)
The article emphasizes the need to form communicative competence in the process of teaching foreign languages to schoolchildren using interactive teaching methods due to the rapid globalization processes, the growing and growing rapprochement of cultures, the social order of the state and society to the level of language and communicative training of a school graduate. The process of teaching foreign languages to schoolchildren is effectively carried out on the basis of systematic, activity and competence-based approaches. If a specially developed educational and methodological complex is used in the organization of the educational process, its tasks are carried out through the use of interactive methods. It is important to organize methods of teaching foreign languages to schoolchildren and the subject-objective interaction between the teacher and the student.
Keywords: Foreign language; communicative competence; teaching foreign languages; Academic lyceum